Obesity in children with Down syndrome: A retrospective review of growth charts and professional recommendations to parents - Nagat Al Kabir (18504997) (2024)
Background Down Syndrome (DS) is the most common genetic disorder. Individuals with DS are susceptible to obesity. The prevalence of overweight and obesity in DS varies from 23% to 70% depending on ethnicity. Obesity is a risk factor for obstructive sleep apnoea, dyslipidaemia, hyperinsulinemia, and gait disorder. We conducted a healthcare compliance audit against the United Nations Children’s Fund (UNICEF) and the World Health Organization’s(WHO) guidance on interventions and prevention of obesity in children. Methods During a 6-year period (2016-2021), 247 DS patients aged 5 to 14 years old were seen in child development clinics. 40% (100 patients) were selected and represented each age group and gender. Electronic medical records were reviewed. We categorized DS patients based on patients’ Body Mass Index (in accordance with WHO definitions of underweight, healthy weight, overweight, obesity, and morbid obesity). Results More than half (57%) of DS patients were overweight to morbidly obese. Of which more boys (45.6%) than girls (21%) were obese to morbidly obese. Interventions including recommendations of healthy eating and/or physical exercise were provided by physicians or nurses to 34% of obese to morbidly obese patients. 15% were referred to Dietetics Services to follow a weight management program. Conclusion Only a third of obese patients received lifestyle recommendations for managing obesity, and less than half of those were referred to Dietetics. We recommend that physicians should increase parental awareness of obesity, discuss healthy lifestyle with parents, and consider referral to weight management services. Nurses have a vital role in health promotion and disease prevention through patient and family education. An evidence-based educational program is required for all nurses. We recommend screening for secondary prevention of diseases in high-risk groups (i.e. dyslipidaemia, hypertension, and diabetes). Further research is encouraged to assess interventions and prevention of obesity in DS.